Distinct Parameters in the EEG of the PLP α-SYN Mouse Model for Multiple System Atrophy Reinforce Face Validity - Härtner, Lorenz; Keil, Tobias W. M.; Kreuzer, Matthias; Fritz, Eva Maria; Wenning, Gregor K.; Stefanova, Nadia; Fenzl, Thomas (Frontiers in Behavioral Neuroscience, 2017)
Multiple system atrophy (MSA) is a neurodegenerative movement disorder characterized by parkinsonian symptoms and cerebellar symptoms. Sleep disturbances also play a crucial role in MSA. One of the most convincing animal models in MSA research is the PLP α-SYN model, but to date no studies on sleep disturbances in this mouse model, frequently found in MSA patients are available. We identified spectral shifts within the EEG of the model, strikingly resembling results of clinical studies. We also characterized muscle activity during REM sleep, which is one of the key symptoms in REM sleep behavioral disorder. Spectral shifts and REM sleep-linked muscle activity were age dependent, supporting face validity of the PLP α-SYN model. We also strongly suggest our findings to be critically evaluated for predictive validity in future studies. Currently, research on MSA lacks potential compounds attenuating or curing MSA. Future drugs must prove its potential in animal models, for this our study provides potential biomarkers.